Hayat Mecmuasında edebi muhteva (şiir ve hikaye, 1926-1929) - Güneş, Mehmet (Marmara Üniversitesi, 2004)
Bu çalışmada Hayat mecmuasındaki telif şiir ve hikâyeler incelenmektedir. Giriş bölümünde mecmua yazarlarının şiir ve hikâyeye dair yazdıkları nazarî yazılar değerlendirildi. Bu yazılarda yazarlar edebî eserin oluşturulması ile ilgili teklifler sundukları gibi, edebî eserlerde gördükleri eksiklikleri de tenkit etmişlerdir. Bu tenkitler polemikleri beraberinde getirmiştir. İkinci bölümde mecmuadaki şiirlerin şekil açısından tasnifi ile muhteva açısından incelenmesinden oluşmaktadır. Şiirler ağırlıklı olarak, ölçü açısından hece ölçüsü ile; kafiyeleniş açısından koşma tipi kafiye ve çapraz kafiye ile yazılmışlardır. Mecmuanın ilk sayılarında sosyal konulu şiirler ağırlıklı iken, sonraki sayılarda ferdî konulu şiirler ağırlıklıdır. Mecmuada şairler çok farklı konularda şiirler yazmışlardır. Şiirlerde en çok kullanılan tema ferdî aşk temasıdır. Farklı temalarda da şiirler yazılmıştır. Mecmuada daha önceki dönemlerde tanınmış Fâruk Nâfiz, Hâlit Fahri, Celal Sâhir, Enis Behiç, Şükûfe Nihâl. gibi şairlerle birlikte Necip Fâzıl, Ahmet Hamdi, Yaşar Nâbi, Sabri Esat, Vasfi Mâhir. gibi şairler de şiirler yazmışlardır. Üçüncü bölümde mecmuadaki hikâyeler incelendi. Mecmuada hikâye sayı bakımından şiire nispetle çok azdır. Hikâyelerde yazarlar umumiyetle sosyal konulara yer vermişlerdir. Hikâyeler o devir hayatına tarihî, ekonomik, sosyal ve siyasî açıdan ışık tutacak niteliktedir. Mecmuada o dönemde meşhur olan Reşat Nûri, Aka Gündüz ile birlikte, Seniha Sami, Fuat Bahattin, Safvet Örfi ve Suat Derviş de hikâye yazmıştır. Mecmuadaki sosyal muhtevalı şiirler ile hikâyeler arasında benzerlikler kendini hissettirmektedir. Sonuç bölümünde bu benzerlikler belirtilmiştir. Çalışmamızın sonuna mecmuadaki telif şiir ve hikâyelerin şair ve yazarlarına göre fihristi verilmiştir. ABSRACT This dissertation examines poems and stories in Hayat journel. The first chapter deals with theoretical texts by Hayat writers. At these texts the writers on the one hand speculates on how to construct a literary work, and criticize deficiencies they found in the works of their time on the other. The Second Chapter analysis contends of poems and classifies them according to their forms. The poems of Hayat are mostly of syllabic meter; koşma and crosswise rhymes. While poems of Hayat were predominantly on social matters in early volumes, individuality dominate on later volumes. The most frequently theme of poems is love, though other themes used as well. Hayat contained on the one hand some known poems of relatively early generation as Faruk Nafiz, Halit Fahri, Celal Sahir, Enis Behic, Sukufe Nihal, and gave a place to those of new generation like Necip Fazıl, Ahmed Hamdi, Yaşar Nabi, Sabri Esat, Vasfi Mahir. In the third chapter, stories were examined. Compared with poems, stories of Hayat are less and dwelled much more on social issues, which shed light on historical, social and political dimensions of their time. In the journel, some fameous Reşat Nuri, Aka Gündüz, and Seniha Sami, Fuat Bahattin, Safvet Örfi and Suat Derviş were also wrote short-story. There are interesting similarities between the stories and poems of social contend. The conclusion focuses on these similarities and analyses them. An index of authors and works in Hayat is added at the end of the dissertation. This dissertation examines poems and stories in Hayat journel. The first chapter deals with theoretical texts by Hayat writers. At these texts the writers on the one hand speculates on how to construct a literary work, and criticize deficiencies they found in the works of their time on the other. The Second Chapter analysis contends of poems and classifies them according to their forms. The poems of Hayat are mostly of syllabic meter; koşma and crosswise rhymes. While poems of Hayat were predominantly on social matters in early volumes, individuality dominate on later volumes. The most frequently theme of poems is love, though other themes used as well. Hayat contained on the one hand some known poems of relatively early generation as Faruk Nafiz, Halit Fahri, Celal Sahir, Enis Behic, Sukufe Nihal, and gave a place to those of new generation like Necip Fazıl, Ahmed Hamdi, Yaşar Nabi, Sabri Esat, Vasfi Mahir. In the third chapter, stories were examined. Compared with poems, stories of Hayat are less and dwelled much more on social issues, which shed light on historical, social and political dimensions of their time. In the journel, some fameous Reşat Nuri, Aka Gündüz, and Seniha Sami, Fuat Bahattin, Safvet Örfi and Suat Derviş were also wrote short-story. There are interesting similarities between the stories and poems of social contend. The conclusion focuses on these similarities and analyses them. An index of authors and works in Hayat is added at the end of the dissertation.